Study on the Microstructure and Wear Resistance of the High-Speed Laser-Cladded Coating on the Cutterhead of Mining Machine - GUO Shirui, DING Shouwen, CUI Lujun, CHEN Shuisheng, DU Quanbin, GUO Chuan, XUE Xiaoqiang (Cailiao Baohu)
To improve the microstructure of the alloy coating and enhance the mechanical properties of the cutter head in coal mining machines，Fe-based alloy cladding layers (S1 and S2) were fabricated on mining cutter head surfaces at two scanning speeds of 0.5 m/min and 12 m/min.The metallographic microstructure， mechanical properties and tribological performance of coatings were systematically characterized by scanning electron microscopy (SEM)， Vickers hardness tester， and X-ray diffraction (XRD).Results showed both coatings exhibited dense microstructures without defects such as pores or cracks.The top layer of both laser-clad coatings consisted of equiaxed crystals， the middle layer was composed of columnar crystals， and the bottom layer consisted of planar crystals.Moreover， the overall microstructure of the S2 coating was finer than that of S1， and the overlay layers were primarily composed of an α-Fe solid solution， Cr2B and FeNi.The γ-Fe phase precipitated in S1， while the diffraction angle of the α-Fe phase in S2 shifted to a lower angle than that of S1.Both coatings had higher microhardness than the substrate，with the S2 coating showing the highest microhardness of 651 HV0.5.The strengthening mechanisms of the coating mainly included grain refinement strengthening and solid solution strengthening.Besides， S2 demonstrated the best tribological performance， and the wear rate of the substrate was 7.3 times that of S2.The wear mechanism of the substrate was adhesive wear， whereas that of the coatings was primarily abrasive wear.